Intellectual property rights, external effects, and antitrust law - Ilkka Rahnasto (Oxford University Press, 2003)
The interplay between intellectual property protection and antitrust rules in the communications industry is examined in this timely book, with particular focus upon the role of externalities in that interplay. There is substantial discussion of the innovation process and of how companies leverage their intellectual property rights in order to obtain market leadership. Particular emphasis is also placed upon how legal doctrines have developed to cope with these issues, and related economic analysis is also discussed